The effect of error aversion climate on impoverished leadership - Liu, Chang-E; Liu, Yunfan; Li, Yulei; Hu, Chenhong; Wang, Shan (Frontiers in Psychology, 2025)
IntroductionImpoverished leadership, as a form of unethical leadership behavior, can have a wide range of negative impacts. It not only affects team morale, work efficiency, cohesion, and trust but also directly influences organizational performance, reputation, and the leader’s own career development. However, previous research has rarely explored the antecedents of impoverished leadership.MethodsBased on social cognitive theory and conservation of resources theory, this study investigated the impact of error aversion climate on impoverished leadership with mixed methodologies (i.e., a scenario experiment and a questionnaire survey).ResultsThe results showed that error aversion climate positively influences impoverished leadership; moral disengagement and ego depletion serve as mediators between error aversion climate and impoverished leadership. Besides, regulatory focus moderate the relationship between error aversion climate and moral disengagement (ego depletion). Specifically, when leaders have high prevention regulatory focus and high promotion regulatory focus, the relationship between error aversion climate and moral disengagement (ego depletion) is stronger. Regulatory focus also moderate the indirect effect of error aversion climate on impoverished leadership through moral disengagement (ego depletion). The indirect effect of error aversion climate on impoverished leadership is stronger when leaders have high prevention regulatory focus and high promotion regulatory focus.DiscussionThe findings provide theoretical guidance for interventions to reduce impoverished leadership and offer new insights for promoting organizational sustainability.